Risk factors for renal scarring and clinical morbidity in children with high-grade and low-grade primary vesicoureteral reflux. Issue 2 (April 2022) - Mathias, Sitarah; Greenbaum, Larry A.; Shubha, A.M.; Raj, John A. Michael; Das, Kanishka; Pais, Priya
Summary: Introduction: Primary vesicoureteral reflux (VUR) is associated with urinary tract infections (UTIs) and renal damage. However, the importance of early diagnosis of VUR has been questioned. Moreover, most studies have few patients with high-grade VUR. Hence, we retrospectively analyzed a large cohort of patients with primary high-grade and low-grade VUR and assessed risk factors for renal damage and clinical morbidity. Material and methods: We included patients (<18 years) at diagnosis with low-grade (1–3) or high-grade (4–5) primary VUR and noted their clinical history and presence of hypertension, low eGFR (<60ml/in/1.73 m 2 ), renal scarring (focal or generalised) and reduced differential renal function (DRF; <45%). Risk factors were assessed (in patients and renal units) by logistic regression and generalised estimating equation. Results: Of 399 primary VUR patients, 255 (64%) had high-grade VUR. Indications for voiding cystourethrogram were recurrent UTI (38%), first UTI (28%) and antenatal hydronephrosis (17%). At diagnosis, 252 (65%) had renal scars (focal in 170 [44%], generalised in 82 [21%]), and 188 (47%) had reduced DRF. High-grade VUR patients were more likely than low-grade VUR patients to have renal scarring (75% vs. 49%, p < 0.01), low eGFR (23% vs. 13%, p = 0.04) and significant hypertension (26% vs. 13%, p = 0.02). High-grade VUR was associated with generalised scars (odds ratio [OR] 11, p < 0.001), focal scars (OR 3.1, p < 0.001) and reduced DRF (OR 2.3, p < 0.001) shown in the table. Male sex was a risk factor for generalised scars (OR 2.3, p = 0.005). Focal scars were associated with recurrent UTIs (OR = 1.8, p = 0.004) and reduced DRF (OR 1.4, p = 0.027). Patients with multiple focal scars were diagnosed at an older age (2 years [1, 4] than those with single scars (1.5 years [1, 4] or no scars (1 year [0, 3]), p = 0.04). Discussion: The prevalence of renal damage and clinical morbidity at VUR diagnosis was higher than other studies. High-grade VUR patients had a greater prevalence of renal damage, low eGFR and hypertension than low-grade VUR patients and was a risk factor for focal scars, generalised scars and reduced DRF. Focal scars were independently associated with recurrent UTI. Those with multiple scars were diagnosed later than those with single scars or no scars. Conclusions: High-grade VUR was associated with renal damage and clinical morbidity. Our study highlights the importance of diagnosing VUR early to identify patients who may warrant long-term follow-up and intervention to minimize morbidity. Summary Table Factors associated with renal parenchymal damage in primary VUR a . Summary Table Factors Patient Renal unit Adjusted Odds Ratio p value Adjusted Odds Ratio p value Generalised scars Male 2.44 0.004 2.29 0.005 High-grade VUR b 5.78 <0.001 11.00 <0.001 Focal scars High-grade VUR b – – 3.10 <0.001 Recurrent UTI 1.88 0.004 1.52 0.020 Symptomatic Antenatal HDN 0.71 0.28 0.49 0.004 Reduced DRF High-grade VUR b 2.12 0.002 2.32 <0.001 Ipsilateral scars – – 1.44 0.027 HDN hydronephrosis, UTI urinary tract infection, VUR vesicoureteral reflux. a Concise version of Table 2 in main manuscript. b Grade 4, 5 VUR.